Evolution and Challenges of Cyber Law in the Digital Era: Case Studies in Developing Countries - Loso Judijanto; Samra Al Kandy; Tamrin Fathoni; Arief Fahmi Lubis (ILAW, 2024)
The research explores the dynamic landscape of cyber law governance in developing nations, specifically focusing on Indonesia, Kenya, and Brazil. Method research employs a normative approach, and the study investigates legislative evolution, implementation challenges, data privacy concerns, cybersecurity infrastructure, international cooperation, and the impact of emerging technologies on cyber law. The result research reveals a complex interplay between legislative advancements and implementation gaps, highlighting the need for stronger regulatory measures to address data privacy issues and enhance cybersecurity readiness. The study also emphasizes the importance of international collaboration and adaptive regulatory frameworks in effectively governing cyberspace in the digital age.